On the Effectiveness of Participatory Approach on EFL Learners' Achievement: EFL Learners' Perceptions in Focus - Fatehi Rad, Neda; Sahragard, Rahman (REVELL - REVISTA DE ESTUDOS LITERÁRIOS DA UEMS, 2018)
The present study aimed to investigate the potential effects of participatory approach on EFL learners’ academic achievement. Moreover, the effects of applying participatory approach on learning English from the learners' perspective were also explored. The participants of the study were 60 Iranian EFL learners from two intact classes. These two classes were randomly assigned to one control group and one experimental group. For fourteen sessions, the researcher in the control group class followed her regular teaching practice through the conventional book-based method of conducting an English class. In the experimental group class; however, the researcher adopted participatory approach tasks and activities, in which she applied various participatory approach-based techniques, activities, role play, and problem solving activities, group work and collaborative tasks in the classroom instruction. Results of the comparison of the effects of the experimental participatory group and the control conventional group revealed that although the students in both groups improved their scores on the IELTS posttest, there was no statistically significant difference between the experimental group’s overall performance and that of the control group. Results of the analyses conducted on separate skills on the IELTS exam; however, revealed that the experimental group had higher scores on the speaking skill in comparison of the scores of the control group. Results of the interview with the students revealed that they held positive attitudes towards implementing the participatory approach and they were willing to be exposed to at least some of the tasks and activities in their future courses. Based on the findings of the current study, teachers are encouraged to use the activities and tasks associated with participatory approach.